Nitrogen and residue management effects on performance of happy seeder sown wheat - SIDHU, AMANDEEP SINGH; KANG, J S; KAUR, JAGROOP (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted during rabi 2016-17 and 2017-18 to evaluate the influence of different residue and nitrogen management practices on soil physico-chemical properties, root density, weed growth and grain yield of happy seeder sown wheat. Experiment was conducted in randomized block design consisting of eleven residue and nitrogen management treatments in four replications. The results inferred that weed biomass was significantly less in chopped straw treatments (C) as compared to unchopped treatments (NC). Treatments receiving 150 kg N/ha had higher root density than 125 kg N/ha treatments at all soil depths during both years. Soil physical and chemical properties were not significantly affected but there was improvement in these properties after two years of residue retention. Grain yield (5.42 and 5.36 t/ha) was maximum in treatment where 150 kg N (30 kg at chopping of straw and 120 kg as per recommendation) was applied along with 5 t/ha FYM (C+N30+120+FYM5), which was significantly better than NC + N125, C + N125, C + FYM5 + N125 and C + N20+105 treatments but statistically at par with rest of the treatments.